Analisis Dampak dan Faktor Penyebab Kekerasan Seksual di Lingkungan Sekolah - Sari, Rizka Puspita; Siti Zahra Bulantika; Tiara Nadalifa (STKIP PGRI Bandar Lampung, 2024)
Sexual violence is still a serious problem, including in educational settings. This study aims to analyze the impact and factors causing sexual violence that occurs in the school environment. The method used in this study is a literature study. The results of the study indicate that sexual violence in the school environment can have an impact on decreasing students' ability to concentrate, decreasing academic grades, loss of learning motivation, inhibiting self-actualization, dropping out of school, fewer opportunities in the world of work, and tarnishing the name of the school. Meanwhile, the factors that cause sexual violence in the school environment are low self-control of the perpetrator, low understanding of physical boundaries, unclear rules in the school, an unsafe school environment, unwise use of social media, tolerance of immoral behavior, difficulty collecting evidence, and the last is the lack of parental role and sexual education.